Research on the spread and countermeasures of COVID-19 using agent-based modeling - Fengtao XIANG; Jiongming SU; Xueqiang Gu; Wanpeng ZHANG (智能科学与技术学报)
Aiming at the problems related to the spread and prevention and control of COVID-19, the COVID-19 epidemic was studied based on agent based modeling thought.Firstly, based on the COVID-19 transmission mechanism, a mathematical model was established on the NetLogo platform to simulate the real process of epidemic spread.Secondly, the impacts of different factors (such as epidemic prevention and control measures, population migration patterns, COVID-19 incubation period, cure period and mortality) were analyzed and evaluated on the spread of the epidemic, so as to understand the core factors affecting the epidemic situation.Then, the internal law of the epidemic spread was analyzed and summarized.